Renoprotective impact of angiotensin 1-7: Is it certain? - Mehdi Nematbakhsh (Journal of Nephropathology, 2019)
The two important arms of renin angiotensin system (RAS) are angiotensin II (Ang II) and angiotensin1-7 (Ang1-7). Both of these peptides are present in the kidney, while the renal hemodynamic responses to these peptides act differently in kidney circulation. For this short-review, we used a variety of sources including PubMed, Google Scholar, and Scopus. Although in normal physiological condition, Ang1-7 has been known as an inactive agent in the renal system, however in past years many experimental and clinical reports indicated the protective role of Ang1-7 in renal hemodynamics and functions under different circumstances. In the current article, the possible renoprotective role of Ang1-7 was briefly reviewed.